A Preliminary Review of the Eastern Pacific Species of Elacatinus (Perciformes: Gobiidae) - Hoese, Douglass F.; Reader, Sally (Revista de Biología Tropical, 2001)
Elacatinus limbaughi is described as new from the Gulf of California. Elacatinus digueti is redescribed and Elacatinus inornatus Bussing is synonymyzed with E. digueti. Data are presented on geographical variation in Elacatinus puncticulatus and E. digueti. Species of the genus Elacatinus are normally associated with coral reefs and several of the species clean parasites from other fishes. Elacatinus is regarded as distinct from Gobiosoma, based on vertebral and other characteristics.